Exploring How Older People Living at Home Alone Occupy Their Time - A Time-Geographic Study - Alison Wicks; Megan Blanchard; Ingeborg Nilsson (Scholarworks @ WMU, 2020)
Background: Knowing what older people choose to do with their time informs occupational therapists in their everyday practice. This study explored how sixteen older Australians living at home alone without support occupied their time. Method: People aged 70 years and older living alone in one's home and receiving no support services were voluntary recruited. The participants completed time-use diaries for 5 days and recorded how, with whom, and where they spent time. Data were coded and analyzed using the software program Vardagen. Results: The participants reported 217 different daily activities. While patterns of daily participation varied, all of the participants spent some time with others and some time away from but near home. The majority of their time was spent alone. On average, the participants reported meaningfulness in their occupations 90% of the days. Conclusion: The study highlighted how older people living at home without support services can meaningfully occupy their time if they have access to personally relevant people and places.